VD_FINDINFO Jug / 2011 / 172 vom 5. Mai 2011 - VD Tribunal cantonal (2011)
IN DUBIO PRO REO, TENTATIVEDROIT PÉNAL, VOLDROIT PÉNAL, AFFILIATION À UNE BANDE, PAR MÉTIER, COAUTEURDROIT PÉNAL | 139 CP, 22 CP, 25 CP, 47 CP, 10 CPP (CH)